Behovet av eget kapital vid köp av jordbruksfastighet - Karlsson, Anders (2008)
My purpose with this study was to find out if it is possible to buy a farm today for a person who want to start a farm but has very little own capital. In old study's they have come to the conclusion that you will need at least 20 % own capital to succeed to management the farm. But in the last year the cost for arable land approxley has increased with 30 % in Sweden and the crops have doubled in price. So it would be interesting to see if the banks have a new vision on the need of the own capital when you buy a farm.